Poncet's Disease: A Case Report. (11th December 2020) - Verma, Henuka; Rajvanshi, Nikhil; Rathaur, Vyas Kumar; Pathania, Monika; Bhat, Nowneet Kumar
Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB). It spreads from one person to the another through the air while coughing, spitting, speaking or sneezing. TB most commonly affects lungs but it can affect any organ system. Diagnosis of TB is made on the basis of microbiological evidence of MTB on microscopic examination, cultures and chest X-rays. Poncet's disease is a separate entity in which joints are involved in the form of joint pain and swelling without any microbiological evidence of MTB. It usually occurs in the background setting of pulmonary TB. This case focuses on importance of considering Poncet's disease in the differential diagnosis of paediatric polyarticular arthritis in TB endemic regions or if there is a history suggestive of TB exposure and infection.